Negative Tax Incidence with Multiproduct Firms - Anna D'Annunzio; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2022)
A fundamental result in the theory of commodity taxation is that taxes increase consumer prices and reduce supply, aggravating the distortions caused by market power. This result hinges on the assumption that each firm provides a single product. We study the effects of commodity taxes in presence of multiproduct firms that have market power. We consider a monopolist providing two goods and obtain simple conditions such that an ad valorem tax reduces the prices and increases the supply of both goods, thereby increasing total surplus. We show that these conditions can hold in a variety of settings, including add-on pricing, multiproduct retailing with price advertising, intertemporal models with switching costs and two-sided markets.
Keywords: D42; H21; H22; 330; commodity taxation; tax incidence; multi-product firms; monopoly